(untitled) (Research, Society and Development, 2023)
The objective of this study was to evaluate the reasons why the elderly do not achieve good therapeutic adherence. A systematic review was conducted in the Medical Literature Analysis and Retrieval System Online (MEDLINE), Scientific Electronic Library Online (Scielo), Brazilian Institute of Geography and Statistics (IBGE), Pubmed, and Google Scholar databases from 2017 to 2022. Thirty papers were identified, observing the established inclusion and exclusion criteria. From the reading about the subject, it was possible to see that the literature on the subject in question is homogeneous, with a consensus that therapeutic adherence is low in the elderly and especially in institutionalized elderly, reporting several factors that contribute to this reality, such as the psychological health of the elderly, their length of hospitalization, relationship with family, among other aspects. The literature review highlights that this reality needs changes in order to observe good therapeutic adherence in the future.